2001
DOI: 10.1002/1522-2632(200104)86:2<147::aid-iroh147>3.3.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ultraviolet Radiation and Nutrient Additions on Periphyton Biomass and Composition in a Sub-Alpine Lake (Castle Lake, USA)

Abstract: Rising levels of ultraviolet radiation (UVR) striking the Earth's surface have led to numerous studies assessing its inhibitory effects on phytoplankton and periphyton in aquatic systems. Mineral nutrients such as nitrogen (N) and phosphorus (P) have been shown to increase aspects of algal metabolism and compensate for UVR inhibition. An in situ substratum enrichment technique and UV shielding was used to assess the effects of nutrient additions on periphyton exposed to different levels of UVR in Castle Lake, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 24 publications
0
12
1
Order By: Relevance
“…5 DISCUSSION Several investigations of the effects of UV radiation by exclusion of ambient UV observed reduced chl a accrual within +UV treatments in lakes Leavit 1996, Francoeur andLowe 1998) and artificial streams (Bothwell et al 1994, Hodoki 2005. In contrast, other studies conducted in lakes (Higley et al 2001, Watkins et al 2001), a wetland (Kahn and Wetzel 1999), and a stream (Hill et al 1997) found no significant differences in periphytic algal biomass between fill ambient sunlight (+UV) and PAR-only (-UV) treatments. In the present study, algal biomass appeared to be unaffected by W exposure.…”
Section: Resultscontrasting
confidence: 97%
See 2 more Smart Citations
“…5 DISCUSSION Several investigations of the effects of UV radiation by exclusion of ambient UV observed reduced chl a accrual within +UV treatments in lakes Leavit 1996, Francoeur andLowe 1998) and artificial streams (Bothwell et al 1994, Hodoki 2005. In contrast, other studies conducted in lakes (Higley et al 2001, Watkins et al 2001), a wetland (Kahn and Wetzel 1999), and a stream (Hill et al 1997) found no significant differences in periphytic algal biomass between fill ambient sunlight (+UV) and PAR-only (-UV) treatments. In the present study, algal biomass appeared to be unaffected by W exposure.…”
Section: Resultscontrasting
confidence: 97%
“…In our experiment, overall algal community composition did not vary strongly by UV treatment, in contrast with some previous studies (Bothwell et al 1993, Francoeur and Lowe 1998, Higley et al 2001. Perhaps the shallowness of the wetland water and the lack of a surface connection to any other body of water restricted the pool of potential algal taxa to those relatively tolerant to UV exposure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most work on UVR in lakes has been focused on planktonic communities [75,76], but periphyton is also at risk to UVR, especially in oligotrophic systems. Although epipelic species may migrate downward into sediments during the daylight to avoid UVR exposure [77], Higley et al [78] reported that Anabaena circinalis, the dominant periphyton species in Castle Lake was sensitive to UVR, possibly because its nitrogen-fixing capacity was inhibited by UVR. The major indirect effect of UVR is via photolysis of DOM [79].…”
Section: Competition For Lightmentioning
confidence: 99%
“…They are also the conduit through which primary production reaches larger predators such as fish, which often have commercial, recreational, and cultural importance for humans. In lakes at high elevations, the biomass of middle and upper trophic levels has been measured only rarely (McNaught et al., ), in contrast with more common measurements of lower trophic level biomass (Higley, Carrick, Brett, Luecke, & Goldman, ; Pugnetti & Bettinetti, ). The spatial distribution of that biomass within high‐elevation lakes has been measured even more rarely (Masson, Angeli, Guillard, & Pinel‐Alloul, ).…”
Section: Introductionmentioning
confidence: 99%